2011
DOI: 10.1111/j.1365-2125.2010.03900.x
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone decreases the inhibitory effect of alprazolam on the release of adrenocorticotropin/cortisol induced by physical exercise in man

Abstract: • This study demonstrates a partial opioid influence in the inhibitory effect of ALP on the release of ACTH/cortisol during physical exercise. AIMSTo establish the possible involvement of alprazolam (ALP) and/or opiates in the mechanism underlying the ACTH/cortisol response to physical exercise. METHODSTests were carried out under basal conditions (exercise control test), exercise plus ALP (50 mg at time -90 min), naloxone (10 mg at time 0) or ALP plus naloxone. Plasma ACTH and serum cortisol concentrations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
3
1
1
Order By: Relevance
“…Animal studies have determined that GABA A receptors are present in the pituitary gland and adrenal cortex (in addition to the adrenal medulla and pancreas) ( 36 38 ). Thus, the present findings extend previous observations ( 29 31 ) and demonstrate the wide-ranging effects of GABA A on downregulating multiple key neuroendocrine responses during exercise.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Animal studies have determined that GABA A receptors are present in the pituitary gland and adrenal cortex (in addition to the adrenal medulla and pancreas) ( 36 38 ). Thus, the present findings extend previous observations ( 29 31 ) and demonstrate the wide-ranging effects of GABA A on downregulating multiple key neuroendocrine responses during exercise.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the importance and frequent activation of GABA A receptors, very little is known about the effects of stimulation of these receptors on subsequent exercise. Only three studies appear to have addressed this question ( 29 31 ), all of which were performed during maximal exercise and reported that alprazolam could blunt catecholamine ( 29 ) or pituitary/adrenal (ACTH, cortisol) ( 30 , 31 ) responses in healthy humans. However, the effects of prior GABA A activation on integrated ANS, neuroendocrine, and metabolic counterregulatory responses during clamped euglycemia under moderately prolonged submaximal exercise conditions appears to be unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although activity levels may also influence the levels of corticosteroids (Coiro et al 2011), our analysis found no connections here between these two factors. This finding suggests that the significant correlation found between HT levels and corticosterone indeed reflects the higher intensity of a negative emotional state experienced by high stereotypers.…”
Section: Discussioncontrasting
confidence: 63%
“…However, autonomic reactions, such as increased heart rate and elevation of corticosteroids, may be similar in response to situations of different emotional quality. For example, the level of cortisol increases after exposure to a threat, but also after physical exercise (Dickerson and Kemeny 2004; Coiro et al 2011). We thus decided to follow others (Mendl et al 2009; Paul et al 2005) in interpreting corticoid levels as an indication of the level of arousal or of the intensity of the emotion that the subject is experiencing, rather than as an absolute representation of an emotional state.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue associated with central proximal regulation is mainly influenced by neurotransmitters and hypothalamic-pitui tary-adrenal (HPA) axis activities. The activation of HPA axis under stressful events, such as strenuous exercises, causes increased stress hormone production such as cortisol (Coiro et al, 2011). Here, both doses of MCL supplementation reduced plasma cortisol.…”
Section: Discussionmentioning
confidence: 88%